The Family in the Mediterranean Welfare States - Naldini, Manuela (The Family in the Mediterranean Welfare States, 2003)
This work analyses in a historical and comparative perspective the relationship between the family and the welfare state in two Mediterranean countries: Italy and Spain. Two aims form the focus of the book. Firstly, to open the black box of the family in welfare state analysis, introducing a focus on inter-generational and kin relations. Secondly, to explain why the southern welfare states have offered very low support to families with children by taking into account several factors: the legacy of fascism, the role of the Church, and the specific role played by leftist parties in defining family policy as labour policy.